1992
DOI: 10.1677/joe.0.1320353
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related peptide might stimulate calcium secretion into the milk of goats

Abstract: Parathyroid hormone-related peptide (PTHrP) has been shown to stimulate the placental calcium pump in pregnant ewes. Recent studies also suggest a physiological role for this peptide during lactation. In the present work, we have studied the possible role of synthetic human PTHrP(1-34), (1-86) and (140-173) fragments on calcium, inorganic phosphorus and magnesium secretion into milk of four adult goats in early lactation. This was done by measuring differences in calcium, inorganic phosphorus and magnesium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…A significant increase in the concentration of PTHrP established in our study in early lactation is in agreement with the study conducted by Lippuner et al (1996) in humans, in which significantly higher PTHrP values were observed in the blood of lactating women than in that of nonlactating ones. The results of our study are probably connected with the role of PTHrP in the mammary gland during lactation, which is assumed to promote calcium transport in milk (Law et al, 1991;Barlet et al, 1992). However, Onda et al (2006) did not establish significant arterial-venous differences in the blood concentration of PTHrP upstream and downstream of the mammary gland as evidence of the release of PTHrP from the mammary gland, possibly as a result of the very low PTHrP concentrations in both arterial and venous blood, which were below the detection limit in their respective tests.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A significant increase in the concentration of PTHrP established in our study in early lactation is in agreement with the study conducted by Lippuner et al (1996) in humans, in which significantly higher PTHrP values were observed in the blood of lactating women than in that of nonlactating ones. The results of our study are probably connected with the role of PTHrP in the mammary gland during lactation, which is assumed to promote calcium transport in milk (Law et al, 1991;Barlet et al, 1992). However, Onda et al (2006) did not establish significant arterial-venous differences in the blood concentration of PTHrP upstream and downstream of the mammary gland as evidence of the release of PTHrP from the mammary gland, possibly as a result of the very low PTHrP concentrations in both arterial and venous blood, which were below the detection limit in their respective tests.…”
Section: Discussionsupporting
confidence: 57%
“…In cows, a positive correlation has been found between PTHrP and calcium levels in milk (Law et al, 1991). Barlet et al (1992) observed an increased calcium concentration in the milk of lactating goats after the administration of human PTHrP (1-34) and (1-86). PTHrP is involved in the regulation of bone metabolism and has direct effects on the bone tissue.…”
mentioning
confidence: 92%
“…Parathyroid hormone-related peptide (PTHrP) is a newly characterized calciotropic factor which was originally isolated from tumors associated with the paraneoplastic syndrome of humoral hypercalcemia of malignancy (Broadus et al, 1988;Martin and Suva, 1989). PTHrP might be the putative calciotropic factor functioning during lactation: it has biological effects very similar to PTH (Horiuchi et al, 1987;Orloff et al, 1989); it is synthetized in lactating mammary tissue (Thiede and Rodan, 1988;Ratcliffe et al, 1992) and increases calcium and phosphorus secretion into milk (Barlet et al, 1992); in rats, serum levels of PTHrP are increased during lactation and this coincides with stimulation of bone resorption (Miller et al, 1991 (Horiuchi et al, 1987). However, PTHrP can increase plasma 1,25-dihydroxyvitamin D 3 concentrations (Horiuchi et al, 1987;Barlet et al, 1990 (Yamamoto et al, 1991) and goats (Ratcliffe et …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lactation requires the active transport of large quantities of calcium for the production of milk (2). The exact regulatory mechanisms behind calcium homeostasis in pregnancy and lactation require further study, but several factors are known to be involved in maintaining a balanced relationship between the large pool of calcium in the skeleton and the much smaller pool in the extracellular fluid.…”
Section: Introductionmentioning
confidence: 99%